2016
DOI: 10.1155/2016/7249848
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Factors Influencing Speech Audiometric Assessment

Abstract: In speech audiometric testing, hearing performance is typically measured by calculating the number of correct repetitions of a speech stimulus. We investigate to what extent the repetition accuracy of Dutch speech stimuli presented against a background noise is influenced by nonauditory processes. We show that variation in verbal repetition accuracy is partially explained by morpholexical and syntactic features of the target language. Verbs, prepositions, conjunctions, determiners, and pronouns yield significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Some previous results for young adults seem to mirror the present pattern: such that subject relative clauses (SR) result in similar perception scores as topic–verb–object sentences (Coene et al . ) or better perception than SVO sentences, in fluctuating, and especially in stationary noise (Uslar et al . : fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some previous results for young adults seem to mirror the present pattern: such that subject relative clauses (SR) result in similar perception scores as topic–verb–object sentences (Coene et al . ) or better perception than SVO sentences, in fluctuating, and especially in stationary noise (Uslar et al . : fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an utterance such as 'The message claimed her attention' will be less difficult to process than 'He claims to know her' because in the latter case the object of the claim is an infinitive clause that enlarges the syntactic domain with its own internal clausal structure ('he' and 'her' being respectively the subject and the object of the verbal predicate 'to know'). Syntactic complexity partially erases the positive effects of context on speech understanding when combined with other perceptual challenges, such as speech noise (Coene et al 2016, Uslar et al 2013 or increased presentation speed, especially for older individuals with hearing loss , Uslar et al 2011, Wingfield et al 2006. Perception becomes more difficult in sentences with a non-canonical word order such as passive clauses (e.g., 'Information will be provided tomorrow') or in sentences with more than one possible verb argument structure (e.g., sentences with the verb to send: 'Sheldon sent the letter' and 'Sheldon sent Debbie the letter') (Uslar et al 2011: 623-624).…”
Section: Syntactic Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…Within our own group, we have recently reported important linguistic effects of test stimuli on hearing performance outcomes for the Dutch-speaking area [19]. Using test sentences with varying degrees of linguistic difficulty at the morpholexical and syntactic levels, we have found that sentence repetition accuracy is significantly lower with verbs than with nouns, adjectives, or adverbs, or with syntactically more complex constructions such as passive sentences (e.g., The document has been released into the public domain) or object relative clauses (e.g., I…”
Section: Discussionmentioning
confidence: 99%